USP21 Promotes the Progression of Nasopharyngeal Carcinoma by Regulating FOXM1 - Xiaofeng Li; Xia Li (Hindawi Limited, 2023)
The purpose of this work was to explore the molecular mechanisms by which USP21 regulates nasopharyngeal carcinoma tumor growth and cancer cell stemness. In this study, the USP21 transcript data was obtained from TCGA database. Then, qPCR and western blot tests revealed that, in contrast to normal tissue or normal nasopharyngeal epithelial cells, the expression of USP21 was greater in nasopharyngeal carcinoma tissues or cell lines, respectively. CCK-8 and EdU immunofluorescent staining assays revealed that USP21 promoted the proliferation of nasopharyngeal carcinoma cells. Meanwhile, scratch and transwell assays showed that USP21 facilitated migration and invasion of nasopharyngeal carcinoma cells. Sphere formation assay was performed on nasopharyngeal carcinoma cells after knockdown of USP21, which revealed that knockdown of USP21 inhibited the stemness profiles of nasopharyngeal carcinoma cells. Then, the western blot assays indicated that knockdown of USP21 in nasopharyngeal carcinoma cells would inhibit FOXM1 expression, and overexpression of FOXM1 could reverse the cell proliferation ability, cell migration and invasion ability, and cell stemness profiles. Finally, a nasopharyngeal xenograft model suggested that USP21 facilitated tumor growth in mice. These findings proved that USP21 promoted tumor growth and cancer cell stemness in nasopharyngeal carcinoma by regulating FOXM1.